Pencapaian Kedaulatan Pangan oleh Masyarakat Adat: Studi Kasus Cireundeu, Leuwigajah, Kota Cimahi - Shafira Dyah Putri Aruman (Global Focus, 2024)
The food sovereignty of the Cireundeu indigenous community in Indonesia integrates cultural values ​​and local geographic conditions in food management. This community relies on cassava (rasi) as a staple food, which is managed independently without relying on the government. The process of food production and distribution is carried out within a family and barter framework, creating a sustainable food system. The implementation of this food sovereignty results in food independence, protects the environment, and strengthens cultural identity. Environmentally friendly agricultural practices, such as avoiding chemical fertilizers and pesticides, maintain the quality of the soil and surrounding animals. Food independence also has a positive impact on the community's economy, by minimizing the risk of rising food prices. The community can develop cassava-based products through the Serba Singkong (SS) UMKM, which helps increase income, especially for mothers. In addition, customary practices that are still preserved attract visits from outside, encouraging the formation of POKDARWIS (Tourism Awareness Group) as a food and environmental tourism destination. Thus, the food sovereignty of the Cireundeu indigenous community not only guarantees food availability, but also contributes to environmental conservation and improving economic welfare, while maintaining a rich cultural identity.   Keywords: food sovereignty, food independence, Cireundeu